A fé como seguimento de Jesus Cristo - Aquino Júnior, Francisco de (Revista Eclesiástica Brasileira, 2013)
No contexto mais amplo da celebração do Ano da Fé, o artigo apresenta a fé cristã como seguimento de Jesus Cristo. Começa tratando da crise de fé que caracteriza nosso tempo e suas possíveis causas: modernidade, fim da cristandade, contratestemunho. Explicita em que sentido a fé deve ser vivida e compreendida como práxis do seguimento de Jesus: é participação na fé de Jesus, é paradoxalmente dom e tarefa, diz respeito à totalidade da vida humana, necessita de muitas mediações práticas e teóricas e tem uma dimensão escatológica fundamental. Aborda os traços e desafios epocais do seguimento de Jesus, seja no que diz respeito a seu núcleo fundamental (fé de Jesus), seja no que diz respeito às características e aos desafios de nosso tempo (o hoje da fé). E conclui insistindo em que o maior desafio pastoral consiste na atualização/encarnação do modo de vida de Jesus em nosso tempo: viver como Jesus viveu, ter a fé de Jesus. Abstract: In the broader context of the celebration of the Year of the Faith, this article presents the Christian faith as the continuation of Jesus Christ. It starts by dealing with the crisis of faith characteristic of our time and its possible causes: Modernity, end of Christianity, counter testimony. It explains how the faith must be lived and understood as praxis of Jesus’ continuation; it is participation in the faith of Jesus, and paradoxically it is a gift and a task; it is concerned with the totality of human life, it needs much practical and theoretical mediation and has a fundamental eschatological dimension. It deals with the epochal traits and challenges of a follow-up of Jesus, either with regard to its fundamental core (faith of Jesus) or with regard to the characteristics and challenges of our time (the nowof the faith). And it concludes by insisting that the greatest pastoral challenge consists in the updating/incarnation of Jesus’ way of life in our times: that is, to live as Jesus lived, to have Jesus’ faith. Keywords: Faith. Modernity. Christianity. Counter testimony. Following Jesus Christ.